Construção participativa de um sistema de informações em uma associação de produtores agroecológicos - Lucena, André Duarte (2010)
Informations permeate productive systems therefore, currently, its management has great relevance. Agroecology has been expanding worldwide, and in Brazil, family farming has a big participation on this production, frequently being held by organizations with associative and cooperative bases. In this context, informations complexity is greater. This work presents the experience of participative building of an Information System (IS) designated to support productive and commercial processes of an agroecological family farmers association in a lowland region of Paraíba (Brazil), the Ecovárzea. The main goal of this research was to develop and experience this process of collective building of an IS. The work was participative and interventionist. In order to reach this goal many methodological practices and tools were used, like: interviews and in loco observations through questionnaire and checklists applications, bibliographical and documental research and, mainly the experience itself. Before initialize the IS building a description of the association and the production system was held, focusing on cooperation aspects and relations of power, as well as historical and socio-political aspects that influence the associations activities. To fulfill the goal of building the system, various activities were carried out: identification of data and information status in the production system; identification of critical information management, election of the aspects to be covered by the system; general definition of the expected system outputs; definition of data to be collected, their means of collection and storage; definition of data treatments; employment of tools and dynamics of data collection analysis, tests and adjustments; implementation of the system in a computer applicative; provision of educational activities for completing the implementation, continuity and improvement of the system. Given the experience of building an information system in a participative way and the reflections generated by the experience, the following conclusion was reached: aspects that drive the actions of individuals and groups, such as history, culture, context and institutions, should be also observed in addition to information, knowledge and practices involved in the production system.